ANALISIS PERLAKUAN AKUNTANSI ASET TETAP PADA CV. XYZ - Ngatimin Ngatimin (PT. Jurnal Center Indonesia Publisher, 2024)
This research was conducted at CV. XYZ using primary and secondary data obtained from the company and focused on accounting treatment, especially fixed asset accounting.The goal to be achieved in this final project is to determine the treatment of fixed assets based on PSAK No. 16 on CV. XYZ. The type of data used is primary data and secondary data. The data collection method used consisted of interview and documentation methods. Primary data used in the form of interviews. While the secondary data used are the financial statements of CV. XYZ in 2017 and a list of fixed assets of CV. XYZ in 2017. The data analysis method used is descriptive qualitative analysis. The results of the preparation of the final project show that the accounting treatment of fixed assets at CV. XYZ is in accordance with PSAK No. 16. CV. XYZ continues to be guided by PSAK No. 16 regarding fixed assets and continues to follow developments so that the financial statements produced remain reliable with accounting guidelines generally accepted. Keywords: Treatment of Fixed Assets, PSAK No. 16